Optimalisasi Limbah Kayu dan Genteng Menjadi Arang Briket untuk Meningkatkan Pendapatan Warga Desa Tamansari - Yuliatin Azizah; Ihsanudin Ihsanudin; Saiful Amin (Jurnal Pelayanan Masyarakat, 2025)
This community service activity aims to optimize the utilization of woodcraft waste and broken tiles in Tamansari Village through training in briquette charcoal production and effective marketing strategies. The wood waste, which has not been optimally utilized and has become an environmental issue, is expected to be processed into high-economic-value products. The conversion of waste into briquette charcoal is expected to reduce pollution while opening up new environmentally-friendly business opportunities. The implementation method includes socialization on the potential and benefits of briquette charcoal, technical training covering material preparation, carbonization process, mixing, molding, and drying, as well as assistance with marketing strategies both offline and digitally. Participants include local residents, small business owners, and craftsmen. The expected outcomes are an increase in the community's skills in processing waste into marketable products, the growth of new businesses based on alternative energy, and increased awareness of environmentally-friendly waste management. This program is expected to make Tamansari Village a model for creative, independent, and environmentally-conscious villages with strong competitiveness in the local economy.